2000
DOI: 10.1007/s001010050814
|View full text |Cite
|
Sign up to set email alerts
|

Der Einfluss verschiedener Volumenersatzmittel auf die Funktion von neutrophilen Granulozyten in vitro

Abstract: The physiological significance of these changes in a range of 10% has to be clarified in further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
1
5
1
3
Order By: Relevance
“…All patients were premedicated with 7.5 mg midazolam p.o., to reach a similar degree of sedation (6). The time and volume schedule was comparable to the previous in vitro study (5). In vitro , an incubation time of 30 min was sufficient to increase expression of complement receptors.…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…All patients were premedicated with 7.5 mg midazolam p.o., to reach a similar degree of sedation (6). The time and volume schedule was comparable to the previous in vitro study (5). In vitro , an incubation time of 30 min was sufficient to increase expression of complement receptors.…”
Section: Methodssupporting
confidence: 72%
“…The result was a number of 15 patients for each group. This calculation was based on our in vitro study (5), in which treatment of whole blood of 10 donors with colloids revealed significant differences. The mean±standard deviation (SD) of MFI was calculated for all parameters at each data point.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of different fluids on immune system response have been demonstrated in vitro and in vivo studies during sepsis, hemorrhagic shock and hemodilution. The activation of the inflammatory system following massive fluid resuscitation is intimately related to negative outcomes (Cotton et al, 2006;Lee et al, 2005;Rhee et al, 1998;Welters et al, 2000). Several studies have shown divergent results because different colloids may bear pro-inflammatory (Alam et al, 2004;Lee, 2005;Rhee et al, 2000) and anti-inflammatory effects (Alam et al, 2000;Jaeger et al, 2001;Lang et al, 2003).…”
Section: The Impact Of Fluid Replacement On Tissuesmentioning
confidence: 99%
“…In four controlled in vitro and animal studies, HES was either proinflammatory (16,22,23) or devoid of anti-inflammatory activity displayed by albumin (21). Two studies showed no difference between HES and albumin in modulation of inflammatory processes (3,11), whereas results of one study were inconsistent (17).…”
mentioning
confidence: 99%